Effects of Consideration of Future Consequences and Temporal Framing on Acceptance of the HPV Vaccine Among Young Adults. Issue 9 (1st September 2016) - Kim, Jarim; Nan, Xiaoli
ABSTRACT: This study examines how individual difference in consideration of future consequences (CFC) and temporal framing (i.e., present- vs. future-oriented message) interact to influence the persuasive outcomes of a health message promoting human papillomavirus (HPV) vaccination among young adults. Results of an experiment ( N = 416) showed a significant interaction effect of CFC and temporal framing on persuasion. The nature of the interaction suggested that individuals with high CFC generally were more persuaded by the present-oriented messages, compared to the future-oriented messages. On the other hand, those with low CFC responded similarly to the present- and future-oriented messages. Implications of the findings for HPV vaccination messaging are discussed.